The effectiveness of the first dose COVID-19 booster vs. full vaccination to prevent SARS-CoV-2 infection and severe COVID-19 clinical event: a meta-analysis and systematic review of longitudinal studies - Xu, Junjie; Lan, Xinquan; Zhang, Liangyuan; Zhang, Xiangjun; Zhang, Jiaqi; Song, Moxin; Liu, Jiaye (Frontiers in Public Health, 2023)
Background: The effect of Coronavirus Disease 2019 (COVID-19) vaccines wanes after the completion of primary COVID-19 vaccination. This study aimed to synthesize the clinical effectiveness of the first dose of COVID-19 booster by comparing it to the full vaccination. Methods: Studies in PubMed, Web of Science, Embase, and clinical trials databases were searched from 1 January 2021 to 10 September 2022. Studies were eligible if they comprised participants who were not ever or currently infected with SARS-CoV-2, did not have impaired immunity or immunosuppression, and did not have severe diseases. The seroconversion rate of antibody to S and S subunits and antibody titers of SARS-CoV-2, frequency and phenotype of specific T and B cells, and clinical events involving confirmed infection, admission to intensive care unit (ICU), and death were compared between the third dose COVID-19 booster group and full vaccination group. The DerSimonian and Laird random effects model were used to estimate the pooled risk ratios (RR) and corresponding 95% confidence intervals (CIs) for the outcomes of clinical interest. While a qualitative description was mainly used to compare and pool the immunogenicity. Results: Of 10,173 records identified, 10 studies were included for analysis. The third dose COVID-19 booster vaccine could induce higher seroconversion rates of antibody against various SAS-CoV-2 fragments, higher neutralization antibody titers against various SARS-CoV-2 variants, and robust cellular immune response compared to the full vaccination. The risk of SARS-CoV-2 infection, the risk of admission to the ICU, and the risk of death were all higher in the non-booster group than those in the booster group, with RRs of 9.45 (95%CI 3.22-27.79; total evaluated population 12,422,454 vs 8,441,368; I2=100%), 14.75 (95%CI 4.07-53.46; total evaluated population 12,048,224 vs 7,291,644; I2=91%), and 13.63 (95%CI 4.72-39.36; total evaluated population 12,385,960 vs 8,297,037; I2=85%), respectively. Conclusion: A homogenous or heterogeneous booster COVID-19 vaccination could elicit strong humoral and cellular immune responses to SARS-CoV-2. Further, it could significantly reduce the risk of SARS-CoV-2 infection and severe COVID-19 clinical event on top of two doses. Future studies were needed to investigate the long-term clinical effectiveness of the third dose of the COVID-19 vaccine.